Identification of missense mutations in genes related to cancer pathways in glioma - Nor Azian Abdul Murad,; Saiful Effendi Syafruddin,; Muhiddin Ishak,; Mohd Ridhwan Abdul Razak,; Sri Noraima Othman,; Soon, Bee Hong; Azizi Abu Bakar,; Farizal Fadzil,; Jegan Thanabalan,; Toh, Charng Jeng; Isa Mohamed Rose,; Roslan Harun,; et al. (Pusat Perubatan Universiti Kebangsaan Malaysia, 2016)
Glioma is the most common primary brain tumour of the central nervous system. Many genetic alterations and mutations have been identified in glioma using various approaches. We performed DNA sequencing on the tumours of 16 patients with Grade I, II, III and IV glioma. The AmpliSeq Cancer Primers Pool was used to generate the amplicons. The targeted-ion sphere particles were prepared using the Ion One Touch and Ion Enrichment systems. DNA sequencing was performed on the Ion Torrent Personal Genome Machine (PGM) and the data were analysed using the Torrent Suite Software. In total, 14 mutations were identified in the following genes: KDR (Q472H), MLH1 (V384D), MET (N375S), PTPN11 (E69K), BRAF (V600E), TP53 (D149E, E154K, V157F), IDH1 (R132H), PIK3CA (H1047R), CSF1R (c1061_1061 ins A), KIT (M541L), PTEN (c1373_1373 del A) and PDGFRA (E556V). In addition, there were four novel mutations identified; TP53 (E154K, and D149E), CSF1R (c1061_1061 ins A) and PDGFRA (E556V). The pathogenicity prediction showed that only three mutations were pathogenic: PTPN11 (E69K), BRAF (V600E) and Tp53 (E154K). These mutations result in changes of the proteins’ structure and could affect their functions. Pathway analyses suggested that these genes are closely related to the pathogenesis of GBM through several pathways such as proliferation and invasion, metabolism and angiogenesis. In conclusion, PGM in combination with the AmpliSeq Cancer Panel could be utilised as a potential molecular diagnostic tool not only for glioma but also for other cancers.